Reflective metasurface for 5G & beyond Wireless communications - Monisha Selvaraj; Ramya Vijay; Rajesh Anbazhagan (Scientific Reports)
Abstract This paper presents a scalable reflective metasurface design optimized for 5G and beyond (B5G) wireless communications, featuring a unique combination of passive metasurface elements. The proposed design emphasizes a less complex structural configuration, facilitating easy scalability and cost-effective fabrication. By implementing a single-layer structure, the metasurface enables straightforward integration with existing B5G infrastructure and demonstrates compatibility with emerging intelligent surface technologies, such as Reconfigurable Intelligent Surfaces (RIS). The dual-polarization capabilities of the metasurface ensure angular stability in reflection, enhancing signal reliability and performance in diverse communication environments. Theoretical analyses, supported by experimental validation, showcase the metasurface’s effectiveness in addressing the challenges of modern wireless communication systems, paving the way for its practical application in next-generation communication.